Differences in Adverse Effect Profiles of Corticosteroids in Palliative Care Patients. (February 2019) - Jaward, Leanna R.; O'Neil, Thomas A.; Marks, Adam; Smith, Michael A.
Background: Corticosteroids are frequently utilized in the palliative care setting to combat symptoms such as fatigue, dyspnea, pain, weakness, anorexia, cachexia, nausea, and vomiting. Often times, adverse effects arise with corticosteroid use, and it is unclear whether switching to another corticosteroid would reduce the risk of specific adverse effects or what measures can be taken to alleviate the adverse effects. Objective: This article aims to review the differentiating pharmacokinetics, potency, and adverse effect profiles of corticosteroids and summarize their clinical applicability. Methods: A literature review of "corticosteroids" and "palliative care" was performed using the PubMed database through July 2018. Original studies relevant to the purpose of this study were identified and those that met inclusion criteria were included. Results: Although corticosteroids share many common factors, including similar pharmacokinetic, pharmacodymanic, and adverse effect profiles, they have significant differences when the details of these variables are reviewed. Providers that prescribe corticosteroids for symptom management should be aware of these differences and the recommended management strategies. Conclusions: Recognition of corticosteroid induced adverse effect profiles and possible management strategies is crucial to optimal symptom management in palliative care patients.